2017
DOI: 10.1155/2017/4863167
|View full text |Cite
|
Sign up to set email alerts
|

Content Downloading with the Assistance of Roadside Cars for Vehicular Ad Hoc Networks

Abstract: Plenty of multimedia contents such as traffic images, music, and movies pose great challenges for content downloading due to the high mobility of vehicles and intermittent connectivity for vehicular ad hoc networks. Roadside units or APs can improve the efficiency of content downloading but with the cost of large investments. In this paper, an efficient content downloading scheme is proposed with the assistance of parking clusters, which are formed by roadside parked cars. After receiving the downloading reque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 22 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…Section II-A first discusses the existing studies on task mapping, and the works on trust evaluation in the vehicular VOLUME 4, 2016 The capability of the computational and storage resources of vehicles has increasingly gained attention in the recent years [22]- [26], where several studies have uncovered the potential of idle vehicle resources for the purpose of content distribution [9], [27]- [33]. Realizing the promising future of smart vehicles, various vehicle clustering algorithms have been proposed to harness its potential in the areas of vehicular routing or vehicle resources.…”
Section: Background Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Section II-A first discusses the existing studies on task mapping, and the works on trust evaluation in the vehicular VOLUME 4, 2016 The capability of the computational and storage resources of vehicles has increasingly gained attention in the recent years [22]- [26], where several studies have uncovered the potential of idle vehicle resources for the purpose of content distribution [9], [27]- [33]. Realizing the promising future of smart vehicles, various vehicle clustering algorithms have been proposed to harness its potential in the areas of vehicular routing or vehicle resources.…”
Section: Background Studymentioning
confidence: 99%
“…Different vehicles have different parking durations with different spatiotemporal conditions, hence their availability for being part of the fog infrastructure also varies. One of the alternatives to solve this problem is using the clustering concept, as clustering the v-fogs can increase service availability through multiple replications and caching [7]- [9]. Other advantages of clustering include having a cluster head to ease management, apart from minimizing collisions in the communication channel to reduce the communication overhead [7]- [9].…”
Section: Introductionmentioning
confidence: 99%
“…The authors of Reference [37] suggest a content downloading method with the help of Roadside cars for Vehicular Ad hoc network. In this research, an efficient content downloading approach is suggested with the assistance of stationary vehicles forming a number of clusters; the vehicles in clusters assist to download the content requested, and pass them to the vehicles in need of it, most especially mobile vehicles.…”
Section: Related Workmentioning
confidence: 99%
“…VANET has two communication scenarios, that is, Vehicle-to-Infrastructure (V2I) and Vehicle-to-Vehicle (V2V), [5]. The cooperative content distribution (CCD) is one of promising VANET applications [6,7]. Operations of CCD are explained in the following.…”
Section: Introductionmentioning
confidence: 99%